Effect of sexed semen on different production and functional traits in German Holsteins. (June 2020) - Diers, S.; Heise, J.; Krebs, T.; Groenewold, J.; Tetens, J.
Highlights: Calf sex had an influence on calving ease and dystocia rates. Sexed semen within same calf sex had only minor effects on most traits. Stillbirth rate for the few male calves from semen sexed for females was 30.6%. Abstract: The aim of this study was to analyze possible effects of semen type (conventional vs. female sexed) and calf sex on fertility and production traits. For this purpose, field data of German Holstein heifers in Lower Saxony were evaluated. Sexed semen was mainly used for first insemination. 87.0% female calves were born from sexed semen, while 52.7% female calves were born from conventional semen. Heifers inseminated with sexed semen were on average 43 to 48 days younger at their first calving than heifers inseminated with conventional semen. Calf sex had an influence on the average calving ease and the dystocia rates. Male calves showed higher calving ease scores and caused a higher risk for dystocia than female calves. The semen type had no influence on these characteristics. Within the same calf sex, sexed semen had only minor effects on most traits, except for stillbirth rates: the stillbirth rate for male calves from female sexed semen was 30.6%, which was 2.86 times the stillbirth rate of male calves from conventional semen, possibly due to trisomies. Sexed semen played only a minor role for production traits in first lactations. The extrapolated 305-day milk yield was 200 kg lower for first calf heifers, which were inseminated with sexed semen compared to heifers inseminated with conventional semen. Fat and protein yield were 6 kg to 8 kg lower after use of sexed semen. Animals with female offspring from sexed semen showed higher survival rates than the other groups.